New Tools for Embryo Selection: Comprehensive Chromosome Screening by Array Comparative Genomic Hybridization. (29th April 2014) - Rodrigo, Lorena; Mateu, Emilia; Mercader, Amparo; Cobo, Ana Cristina; Peinado, Vanessa; Milán, Miguel; Al-Asmar, Nasser; Campos-Galindo, Inmaculada; García-Herrero, Sandra; Mir, Pere; Simón, Carlos; Rubio, Carmen
Abstract : The objective of this study was to evaluate the usefulness of comprehensive chromosome screening (CCS) using array comparative genomic hybridization (aCGH). The study included 1420 CCS cycles for recurrent miscarriage (n = 203 ); repetitive implantation failure (n = 188 ); severe male factor (n = 116 ); previous trisomic pregnancy (n = 33 ); and advanced maternal age (n = 880 ). CCS was performed in cycles with fresh oocytes and embryos (n = 774 ); mixed cycles with fresh and vitrified oocytes (n = 320 ); mixed cycles with fresh and vitrified day-2 embryos (n = 235 ); and mixed cycles with fresh and vitrified day-3 embryos (n = 91 ). Day-3 embryo biopsy was performed and analyzed by aCGH followed by day-5 embryo transfer. Consistent implantation (range: 40.5–54.2%) and pregnancy rates per transfer (range: 46.0–62.9%) were obtained for all the indications and independently of the origin of the oocytes or embryos. However, a lower delivery rate per cycle was achieved in women aged over 40 years (18.1%) due to the higher percentage of aneuploid embryos (85.3%) and lower number of cycles with at least one euploid embryo available per transfer (40.3%). We concluded that aneuploidy is one of the major factors which affect embryo implantation.